Preparing future teachers for interdisciplinarity – designing and implementing a course for pre-service upper secondary teachers - Jankvist, Uffe Thomas; Nielsen, Jan Alexis; Michelsen, Claus (NOMAD Nordic Studies in Mathematics Education, 2013)
Educational researchers and policy-makers have for some time touted the need for interdisciplinary teaching. But while there are many educational, democratic, and economic arguments for bringing an increased attention to interdisciplinary teaching, there has been a striking lack of exposure of the question of how future teachers, who are largely educated in a mono-disciplinary fashion, can best become equipped to introduce genuinely interdisciplinary teaching activities to their future students. This article presents some preliminary reflections upon a graduate course at the University of Southern Denmark, which aims to prepare future science and mathematics teachers for interdisciplinary teaching, and which has been designed on the basis of influential theoretical expositions of the concept of interdisciplinarity.